The Effect of Variations of Mussels and Egg Shells on SCC (Self-Compacting Concrete) - Damara, Yusril; Fahrudin, Muhammad; Haryani, Susi; Setiawan, Randy (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
Self-Compacting Concrete (SCC) could flow and fill molds without compaction (vibrator). use of cement in concrete mixes is crucial, resulting in increasing construction projects. Therefore, ideas or innovations are needed to reduce cement use by utilizing shellfish and eggshells as cement substitutes. This study used a quantitative method taken through experiments aimed at observing the effect of adding shells and eggshells as cement substitutes in Self-Compacting Concrete (SCC) concrete, with variations in eggshell substitution of 0%, 1.5%, 2.5%, 3.5%, and 4.5%, as well as a shell substitution of 5%, with a concrete compressive strength of 21 MPa, made of cylinders with a diameter of 15 cm and a height of 30 cm, testing fresh concrete using the slump flow method and concrete compressive strength testing was carried out at the ages of 3 days, 7 days, and 28 days. The compressive strength test results for the 28-day immersion in PDAM water yielded a maximum concrete compressive strength of 39.71 MPa at the 1.5% variation, and a minimum compressive strength of 31.22 MPa. The 7-day immersion in PDAM water yielded a maximum compressive strength of 26.35 MPa at the 1.5% variation, and a minimum compressive strength of 21.76 MPa at the 4.5% variation. Furthermore, for the 3-day immersion, the highest compressive strength at the 1.5% variation, with a compressive strength of 27.50 MPa, and the minimum achieved at the 4.5% variation, with a compressive strength of 24.07 MPa.